2022
DOI: 10.17509/ijal.v11i3.34667
|View full text |Cite
|
Sign up to set email alerts
|

Teacher readiness and challenges in creating learner autonomy in ICT-based English learning activities

Abstract: The significance of learner autonomy in today’s English Language Teaching (ELT) context has been well recognized and confirmed by many research findings; however, in some cases in which independent learning is not well established, the implementation may not be easy. Thus, this research is intended to provide data on teachers’ readiness and challenges in promoting learner autonomy during online learning activities. This research employed quantitative and qualitative data collection. The quantitative data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Considering its importance, more opportunities to promote students' practical skills in managing their learning should be made (Tuan, 2021), especially through textbooks (Crawford, 1995) on the sections of timetables, tasks, materials/topics, and conversations (Cotterall, 1995). Moreover, research by Maryono and Lengkanawati (2020) and Syafryadin et al (2022) revealed that although online resources may support LA, most teachers found it less preferable to implement online learning activities, as the internet connection was not always stable. In this situation, textbooks play a major role to be the alternatives to support LA.…”
Section: Discussionmentioning
confidence: 99%
“…Considering its importance, more opportunities to promote students' practical skills in managing their learning should be made (Tuan, 2021), especially through textbooks (Crawford, 1995) on the sections of timetables, tasks, materials/topics, and conversations (Cotterall, 1995). Moreover, research by Maryono and Lengkanawati (2020) and Syafryadin et al (2022) revealed that although online resources may support LA, most teachers found it less preferable to implement online learning activities, as the internet connection was not always stable. In this situation, textbooks play a major role to be the alternatives to support LA.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the previous research that teachers' roles in promoting autonomous language learning comprised of three types, namely facilitator, counsellor, and resource (Alonazi, 2017;Shi & Han, 2019;Tran & Duong, 2020;Yasmin et al, 2017) and that the promotion of learner autonomy relies greatly on the teachers' awareness of these crucial roles (Alonazi, 2017;Basri, 2020;Tran & Duong, 2020). Therefore, since the English student teachers are the ones who will interact regularly with the students in their future teaching, they are expected to develop the ability to stimulate their students' autonomy in learning which will then in turn promote themselves to possess selfdetermination motivation (Duchatelet & Donche, 2019;Gillison et al, 2019;Ryan & Deci, 2000;Syafryadin et al, 2022;Yu, 2020). Thus, this result corroborates the findings of a great deal of the previous work in the sense that English student teachers need to understand and nurture their significant roles and support their students' processes of decision making and stimulate their interest in learning by being a facilitator, care for their students' needs by being a counselor, and become a resource who provides knowledge, references, and additional materials for their students' learning (Raya & Vieira, 2015;Nguyen & Gu, 2013;Senad et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, in many instances, it can be deduced that the learners have accessed blogs (their own and others') by means of a desktop or laptop computer. In the study described in this article, the participants' access to the internet, as well as the means by which they could do this, were important considerations, due to issues including geographical location, sociocultural factors, and pedagogical practices that have been widely reported to limit access to digital engagement in many contexts (see for example, Cook et al, 2011;Syafryadin et al, 2022;Winthrop & Smith, 2012).…”
Section: Why Smartphones?mentioning
confidence: 99%